Stability and antioxidant activity of phenolic compounds during in vitro digestion. Issue 2 (8th January 2023) - Li, Chun Xiao; Wang, Fu Rong; Zhang, Bing; Deng, Ze Yuan; Li, Hong Yan
Abstract: The impact of phenolic compounds on the human body depended on the type, content, bioavailability, and antioxidant activity. After digestion, different phenolic compounds had different changes of bioavailability and antioxidant activity, which needed to be considered in the application. In this experiment, the structural stability and antioxidant activity of 27 phenolic compounds (phenolic acids, flavonols, flavonoids, and flavanones) were investigated during the in vitro simulated digestion. This experiment eliminated the influence of food matrix, provide a basis for regularity for the changes of phenolic substances in different materials. Results showed that the bioaccessibility of phenolic compounds with different structures varied, and there was a conformational relationship between the structure and stability. After oral digestion, most of the phenolic compounds underwent degradation and the cellular antioxidant activity (CAA) values decreased to a large extent ( p  < 0.05). After gastric digestion, the content ( p  > 0.05) and CAA values ( p  < 0.05) of most phenolic compounds increased. However, after intestinal digestion, the phenolic compounds were degraded to a greater extent, and different structures of phenolic compounds had different changes in CAA values ( p  < 0.05). In general, the CAA values of most phenolic compounds after in vitro digestion were lower than the initial value. The 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH), 2, 2′‐azino‐bis (3‐ehylbenzthiazoline‐6‐sulfonic acid) (ABTS), and ferric reducing antioxidant power (FRAP) values of phenolic acids and flavonols decreased after in vitro simulated digestion ( p  < 0.05), while the values of DPPH, ABTS, and FRAP of most flavonoids ( p  < 0.05) increased. The increased oxygen radical absorption capacity (ORAC) values were found in most phenolic acids, flavonols, and flavonoids ( p  < 0.05), and most flavanones showed unremarkable changes in ORAC values ( p  > 0.05). In general, the changing trend of chemical‐based antioxidant activity was consistent with the content of phenolic compounds.